Principles for the Europeanisation of Public Administration: In Search of the European Procedural Administrative Principles - Gerencsér, Balázs Szabolcs (Public Governance, Administration and Finances Law Review, 2023)
Administrative regimes are no longer isolated phenomena: they are constantly confronted with international influences, which shape the internal structure and system of the states. The cooperation between the European Union and the Member States’ administration is today a kind of convergence in principles. This is what the EU expects from the candidate countries and in the neighbourhood policy. The main question of the study is whether the content of the principles used by the EU is cognisable and consistent. The study covers two policy instruments: the SIGMA project, which is a joint EU–OECD collaboration, and the comparative legal activities of the ReNEUAL. These instruments testify two completely different attitudes: one does not explain the principle but holds it accountable, the other seeks the means to understand its content and the reasons for the differences in interpretations. Both programs have undergone internal development, but while SIGMA has moved away from its administrative procedural roots, ReNEUAL has confirmed it. The paper is another argument in favour of the need for administrative research using the tools of comparative law.